Targeted BiTE expression by an oncolytic vector augments therapeutic efficacy against solid tumors - Speck, Tobias; Heidbüchel, Johannes P. W.; Veinalde, Rūta; Jäger, Dirk; Kalle, Christof von; Ball, Claudia R.; Ungerechts, Guy; Engeland, Christine Elisabeth (Clinical cancer research, 2018)
PURPOSE: Immunotherapy with bispecific T cell engagers has achieved striking success against hematological malignancies, but efficacy against solid tumors has been limited. We hypothesized that oncolytic measles viruses encoding bispecific T cell engagers (MV-BiTEs) represent a safe and effective treatment against solid tumors through local BiTE expression, direct tumor cell lysis and in situ tumor vaccination. EXPERIMENTAL DESIGN: To test this hypothesis, we generated MV-BiTEs from the Edmonston B vaccine strain to target two model antigens. Replicative and oncolytic potential were assessed by infection and cell viability assays, respectively. Functionality of virus-derived BiTEs was tested in vitro by complementary binding and cytotoxicity assays. In vivo efficacy of MV-BiTE was investigated using both syngeneic and xenograft mouse models of solid cancers. RESULTS: We verified secretion of functional BiTE antibodies by MV-BiTE-infected cells. Further, we demonstrated therapeutic efficacy of MV-BiTE against established tumors in fully immunocompetent mice. MV-BiTE efficacy was associated with increased intratumoral T cell infiltration and induction of protective anti-tumor immunity. Additionally, we showed therapeutic efficacy of MV-BiTE in xenograft models of patient-derived primary colorectal carcinoma spheroids with transfer of PBMCs. CONCLUSION: MV-BiTE treatment was effective in two distinct models of solid tumors without signs of toxicity. This provides strong evidence for therapeutic benefits of tumor-targeted BiTE expression by oncolytic MV. Thus, this study represents proof of concept for an effective strategy to treat solid tumors with BiTEs.